The Influence of DKUPP Performance Quality on Service Quality of E-UMKM through Performance Management in Probolinggo City (Jurnal MSDA (Manajemen Sumber Daya Aparatur), 2023)
The performance of government state officials needs to be improved as they shall deliver quality public services. In particular, public service improvement should regard the advancements of information communication technology and utilize innovative programs. The government of Probolinggo City has launcehed E-UMKM card program as an innovative program. E-UMKM card program plays a pivotal role in supporting and empowering micro, small, and medium enterprises (MSMEs). This research was conducted to investigate the influence of state officials’ performance quality on service quality, with a specific focus on performance management. This descriptive quantitative was conducted between January and February 2023 in Probolinggo City. Questionnaires, observation, and documentation techniques were employed for data collection from 100 respondents, which were subsequently analyzed using Smart-PLS. The findings revealed that the Performance Quality of DKUPP Probolinggo City State Officials can positively impact the improvement of Public Service Quality moderated by performance management in the E-UMKM Card Program. ABSTRAK Aparatur negara dalam pemerintahan bekerja dengan memberikan pelayanan publik. Kinerja aparatur negara perlu ditingkatkan untuk meningkatkan Service Quality yang lebih baik. Hal ini juga berkaitan dengan performance management sebagai bentuk penyelenggaraan pelayanan sektor publik oleh para aparatur negara. Terutama pelayanan publik yang dikembangkan sesuai dengan perkembangan tekonologi informasi komunikasi melalui program inovasi. Salah satu inovasi yang dilakukan oleh Pemerintah Kota Probolinggo adalah adanya program kartu E-UMKM. Kartu E-UMKM digunakan sebagai dukungan optimal dalam pengembangan dan pemberdayaan UMKM. Sehingga penulis melakukan riset tentang pengaruh Officials’ Performance Quality terhadap Service Quality yang diperkuat dengan manajemen kinerja. Riset ini termasuk pada riset dengan pendekatan kuantitatif deskriptif dengan teknik kuesioner, observasi, dan dokumentasi. Riset ini diselenggarakan pada bulan Januari dan Februari di Tahun 2023. Penghimpunan data sebanyak 100 responden, diolah menggunakan Smart-PLS. Hasil penelitian memaparkan bahwa Officials’ Performance Quality DKUPP Kota Probolinggo dapat memberikan pengaruh dalam peningkatan Public Service Quality dengan dimoderasi oleh Performance Management Pada Program Kartu E-UMKM.